O controle de constitucionalidade na arbitragem: um estudo à luz da experiência no direito estrangeiro - Maluf, Fernando Del Picchia (2020)
The present study aims to analyze the possibility of constitutionality control by the arbitrator. In the first part of this work, basic preliminary notions are analyzed, such as the concept of Constitution, its normative strength, supremacy and rigidity, as well as terminological issues and its historical contours. In the second part of this work, we then proceed to the study of the different contemporary constitutionality control models. That done, a practical analysis of the control of constitutionality is carried out, which is exercised today, in the Judiciary, in the light of comparative law, with a view to comparing them, ahead, with the control of constitutionality in arbitration. In the third and last part of this work, the theoretical and practical aspects of constitutionality control in arbitration are analyzed. Based on the premises based on the control of constitutionality by judges and courts, the possibility of control by the arbitrator is assessed, tracing preliminary theoretical notions about arbitration as jurisdiction and the arbitrator as a judge of fact and of law and adding theories adopted in international law regarding the control models in the arbitral jurisdiction. However, right after that, the examination of cases taken from foreign law is added to the theory, in which, to a greater or lesser extent, it was decided whether, when, how and to what extent the arbitrators could, in the arbitration, do the constitutionality control. The conclusion reached with this analysis, for the reasons developed throughout the work, is that the arbitrator can not only, but must exercise control of constitutionality in the arbitration jurisdiction